The theory of everything [videorecording (DVD)] - Redmayne, Eddie, 1982-; Jones, Felicity; Prior, Tom, 1992-; Perry, Sophie; Hawking, Jane (Universal Studios Home Entertainment, 2015)
The story of renowned astrophysicist Stephen Hawking, who falls deeply in love with fellow Cambridge student Jane Wilde. Once a healthy, active young man, Hawking received an earth-shattering diagnosis at 21 years of age. With Jane fighting tirelessly by his side, Stephen embarks on his most ambitious scientific work, studying the very thing he now has precious little of: time. Together, they defy impossible odds, breaking new ground in medicine and science.